2011
DOI: 10.1002/adsc.201100206
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active Metal‐Free Catalysts for Hydrogenation of Unsaturated Nitrogen‐Containing Compounds

Abstract: New highly active ansa-ammonium borate catalysts for the direct metal-free hydrogenation of imines were prepared by tuning of the basicity and steric bulkiness of their amine moieties. The highest catalytic activity among previously reported organocatalytic systems was shown for a wide range of nitrogen-containing substrates. The first example of asymmetric imine hydrogenation based on the ansaammonium borate concept was demonstrated. Furthermore, effective catalyst recovery by extraction of the acidic solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
100
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 185 publications
(108 citation statements)
references
References 53 publications
3
100
0
5
Order By: Relevance
“…60 Similarly, Repo et al 61 reported the use of a chiral Nheterocyclic N/B FLP to reduce ketimines, achieving up to 37% ee.…”
Section: Figurementioning
confidence: 99%
“…60 Similarly, Repo et al 61 reported the use of a chiral Nheterocyclic N/B FLP to reduce ketimines, achieving up to 37% ee.…”
Section: Figurementioning
confidence: 99%
“…Repo et al [27] re-investigated Piers N/B system 3 (Scheme 1) and found that it can be converted into a H 2 -activating system by formally exchanging the weak -NPh 2 base component for more Lewis basic alkylamines. The systems 12-14 (Scheme 4), among others, cleave dihydrogen efficiently under mild conditions and have served as active catalysts for imine hydrogenation at elevated temperatures (ca.…”
Section: Hydrogen Splitting and Metal-free Hydrogenationmentioning
confidence: 99%
“…These compounds show reduction activity resembling that of inorganic borohydrides like NaBH 4 , i. e. they are suitable mostly for reduction of polarized multiple bonds. Imines, enamines, silyl ethers 4, 5,6 , α,β-enones 7 , ynones 8 , Nalkylanilines 9 were hydrogenated using stoichiometric or catalytic amounts of FLPs. Due to heterolytic nature of FLP-H 2 adducts, hydrogenation of unactivated multiple C-C bonds using FLPs has some natural limitations, since during the respective step of the catalytic cycle a proton transfer from catalyst to substrate should take place (Fig.…”
mentioning
confidence: 99%